The Detrimental Effect of Titanium Dioxide Nanoparticles on Liver, Kidney and Lipid Profile of Albino Mice Intraperitoneal Exposure - Alsiadi, Wasan A. Wahab; Elhaboby, Ban Talib; Alsamawi, Ali Ibrahim (Al-Mustansiriyah Journal of Science, 2025)
Background: Titanium dioxide nanoparticles (TiO2 NPs) have widespread use in industrial and biological fields owing to their distinctive physicochemical characteristics. Nonetheless, their growing prevalence raises concerns over their possible toxicological impacts, especially on the functionality of essential organs. Objective: The present work examines the subacute toxicity of TiO2 nanoparticles on hepatic and renal function and modifications in the lipid profile in a mouse model. Methods: Forty-eight adult female albino mice were divided randomly into three groups (n=16 each). Two groups were treated intraperitoneally with TiO2 NPs at 100 mg/kg and 400 mg/kg, respectively, while the control group was treated with distilled water. The animals were sacrificed after 7 and 21 days of treatment. Serum levels of urea, creatinine, aspartate aminotransferase (AST), alanine aminotransferase (ALT), and lipid profile parameters (cholesterol, HDL, LDL) were estimated. Results: Both treated groups showed significant rises in urea, creatinine, AST, and ALT levels (p<0.0001) compared to the control. These were more pronounced at higher concentrations and longer exposure durations. Cholesterol level fell after 21 days, with significant drops in HDL and rises in LDL (p<0.0001). Conclusions: TiO2 NPs induce dose- and time-related alteration of liver and kidney function, and lipid metabolism in mice. These findings highlight that further toxicological research on nanoparticle exposure in environmental and biomedical applications is needed.